WEBGIS PEMETAAN TREND KEJADIAN STUNTING PROVINSI JAWA TENGAH 2015-2017 - Vilda Ana Veria, S.Gz, M.Gizi; Bambang Agus Herlambang; Ahmad Khoirul Anam (VISIKES: Jurnal Kesehatan Masyarakat, 2020)
Stunting is a chronic nutritional problem and needs to be addressed immediately. This study aims to map the distribution of the prevalence of stunting in all districts / cities in Central Java province based on the criteria of community nutrition problems by WHO, namely if the region> 20% then the region must immediately make an intervention effort to reduce its prevalence. The design of this study uses research and development using Quantum GIS software. The variable studied was secondary data on the prevalence of stunting in 35 districts/ cities in Central Java Province from 2015-2017. The flowchart of making a geographical system was arranged in a flowchart. Areas with stunting conditions <20% in 2015 in Purbalingga, Kudus, Semarang, Pemalang, Tegal, Surakarta and Semarang City; in 2016 in Banyumas, Magelang, Kendal, Semarang, Semarang City, Salatiga, Semarang City and 1 green zone area (<10%) in Pati; In 2017 all regions in Central Java are chronic. Based on mapping in 2015, the most yellow zone in number among other years. In 2016, the yellow zone shifted to another region and there was one green zone. Whereas in 2017, all regions were in the red zone. Keywords: stunting, Geographic information system, webGIS, Jawa Tengah